Dell’eccezione e dei suoi crocevia: Kierkegaard e Schmitt a confronto - Cancellieri, Federica (B@belonline, 2024)
The essay examines the concept of exception – closely and inseparably connected to that of decision – in the thought of the jurist and political scientist Carl Schmitt and the existentialist thought of Sören Kierkegaard. Schmitt, in Politische Theologie, a famous writing published in 1922, takes up a passage from Kierkegaard’s La Ripresa, without explicitly mentioning the Danish philosopher and limiting himself to referring to him as a ‘Protestant theologian’. Although the concept of exception as Schmitt intends it, and therefore uses it, is placed on the political level while Kierkegaard’s one is existential, the essay aims to highlight the points of contact and those of discontinuity examining above all the studies conducted by Michele Nicoletti, who outlines and points out the link between the two thinkers.